2015
DOI: 10.7763/joebm.2015.v3.264
|View full text |Cite
|
Sign up to set email alerts
|

Study of Customer Satisfaction in the Banking Sector in Libya

Abstract: Abstract-The purpose of this paper is to evaluate the customer satisfaction of the banks sector in Libya, based on customer perception regarding service quality. This is an empirical study using mainly primary data collected through a well-structured questionnaire. The questionnaire has been personally administered on a sample size of 150 bank customers. This paper makes a useful contribution as there are only a few studies dealing with the assessment of service quality in banking sector of Libya. The findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 17 publications
(15 reference statements)
2
15
0
Order By: Relevance
“…Al-Azzam and Fattah (2015) in their study on the effect of service quality dimensions on customer satisfaction among Arab bank customers in Jordan, indicated that all the five dimensions of service quality have a positive effect on customer satisfaction. The findings support prior studies by Kheng, (2010) and Murugiah and Akgam (2015) who found a positive relationship between customer satisfaction and the five dimensions of service quality. These studies confirmed that the five dimensions of service quality are an important tool for assessing the quality of services in the banking sector but the mediating effect of service quality on the relationship between CRM and customer satisfaction was not assessed, hence the gap addressed in this study.…”
Section: Customer Relationship Management Service Quality and Customsupporting
confidence: 90%
“…Al-Azzam and Fattah (2015) in their study on the effect of service quality dimensions on customer satisfaction among Arab bank customers in Jordan, indicated that all the five dimensions of service quality have a positive effect on customer satisfaction. The findings support prior studies by Kheng, (2010) and Murugiah and Akgam (2015) who found a positive relationship between customer satisfaction and the five dimensions of service quality. These studies confirmed that the five dimensions of service quality are an important tool for assessing the quality of services in the banking sector but the mediating effect of service quality on the relationship between CRM and customer satisfaction was not assessed, hence the gap addressed in this study.…”
Section: Customer Relationship Management Service Quality and Customsupporting
confidence: 90%
“…On the contrary, Murugiah and Akgam (2015) concluded an interesting result. They proved a negative relation between bank security and customer satisfaction.…”
Section: Introductionmentioning
confidence: 92%
“…However, various studies (Fraering and Minor, 2013;Murugiah and Akgam, 2015;Cohon, 2007;Zamazalová, 2008) did not confi rm this relations and showed that even satisfi ed customers switch their bank if another one offers them a better product. There are two ways to explain these fi ndings.…”
Section: Introductionmentioning
confidence: 99%